A STUDY OF THE RELATIONSHIP BETWEEN SCHOOL CLIMATE AND STUDENTS’ SCHOOL LIFE SATISFACTION IN WU HAN CHINA-BRITAIN INTERNATIONAL SCHOOL - Long, Li; Eamoraphan, Suwattana (Scholar: Human Sciences, 2015)
The purpose of the study was to study the relationship between School Climate and Students’ School Life Satisfaction in Wu Han China-Britain International School. The research objectives were 1. To identify the level of school climate in Wu Han China-Britain International School. 2. To identify the level of students’ school life satisfaction in Wu Han China-Britain International School. 3. To determine the relationship between school climate and students’ school life satisfaction in Wu Han China-Britain International School. There were two set of questionnaire: school climate survey and students’ school life satisfaction survey. 88% of the questionnaires were returned valid and mean, standard deviation and Pearson’s Correlation Coefficient (r), and regression analysis analyzed questionnaires. The research finding for objective 1: The level of each dimension of school climate were “moderate”, the overall school climate level were “moderate”. The research finding for objective 2: the level of students’ school life satisfaction was “high”. The research finding for objective 3: there was a significant relationship between school climate and students’ school life satisfaction, and the school climate can prediction students’ school life satisfaction. Discussion and Recommendation were provided by the researcher.